The Role Of Zinc Sulphate And Omega 3 On The Improvement Of Weight And Speed Conversion Conversion On Tuberculosis Parent Patients At Surabaya Park Hospital, 2015 - Durry, Fara Disa; Wirjatmadi, Bambang; Adriani, Merryana (Universitas Wijaya Kusuma Surabaya, 2018)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, can affect almost all organs of the body with the most locations in the lungs. Immunity and high nutrients such as vitamin C, zinc and other antioxidants have shown good effects for infections, including tuberculosis. One effort to help accelerate sputum conversion of people with pulmonary tuberculosis is by supplementation of Zinc Sulphate and Omega 3.Objective: Analyze the role of Zinc Sulphate and Omega 3 on sputum conversion acceleration in patients with pulmonary tuberculosis at Surabaya Paru Hospital 2015.Method: This research use Randomized Pre Post Test Post Control Group Design design. In patients with pulmonary tuberculosis with Zinc Sulphate and Omega 3 in the treatment and placebo group in the control group. A sample of 20 patients consisting of 10 treatment patients and 10 control patients. Statistical test using paired T-Test, Friedman test and Mann whitney.Results: Friedman test showed that in the treatment group showed significant difference in the number of BTA between before and after supplementation (p=0,001), while in the control group significance of 0.141. Mann-Whitney testÂ showed no significant difference in the amount of reduction of BTA between the treatment group and the control group (p = 0.080). This means that statistically does not show any significant difference.Conclusions: Zinc Sulphate and Omega 3 play a role in accelerating sputum smear conversion of respondents. The results of smear test in pulmonary TB patients with Zinc Sulphate and Omega 3 supplementation showed positive results